The relation among the setter position, setter height and game result in elite women volleyball - Akarcesme, C.; Yildiran, I.; Bakir, A.; Arslan, Y. (Annals of Ovidius University Constanta-Series Physical Education and Sport/Science, movement and health, 2010)
The setter has an important role in the game result in terms of not only the playing position but also the physical characteristics. In this study, the relationship between the variable of win-lost points of the team as the setter in 6 different positions, setter height, and starting position of the setter and the variable of game result is examined. METHODS. The study is carried out with the data obtained from the records of match analysis concerning 164 plays and 82 matches of 8 teams which were entitled to play in the playoffs from 12 teams of Turkish Women Volleyball League 1. RESULTS. In accordance with the obtained findings, a statistically significant difference between the setter height and the game result is obtained. In addition, there is a significant difference between the win-lost points of team and front or back position of the setter. The same relationship for medium and tall setters is not so significant statistically. Nevertheless, it is observed that the difference between the points which team win or lose when the setter is back player and the points which team win or lose when the setter is front player is statistically significant. A significant relationship between the setters` starting position and the game result is obtained at the level of 0.10. Besides, a significant relationship is observed between the total average win-lost points when the setter is front and back player at the level of 0.10. It is also detected that the average win-lost points when the setter is a back player is greater than the average win-lost points when the setter is a front player. CONCLUSIONS. These findings show that considering the setter`s starting position together with the setter`s height will have a significant effect on the play while creating new tactics.